(untitled) (Sociologisk Forskning, 2022)
In this article, which was delivered as a keynote address at the annual meeting of the Swedish Sociological Association on March 16, 2022 in Uppsala, the following argument is made. Two different approaches to theory in sociology are presented and discussed: theory as text and theory as activities. In the former, theory is seen as embodied in a text, and the focus is squarely on its content. Little attempt is made in the text to discuss how the theory was actually developed and how to use it. In theory as activities, in contrast, the main focus is on how to work with a theory in a concrete manner. The basic unit of analysis is here not just the theory, but the theory as part of the research process. Theory, method and facts are all linked together in this process and partly overlap. A number of activities that precede the publication of a theory as well as come after are also explored. The concluding pages contain a discussion of the advantages and disadvantages that come with working with each of the two views of theory.